Vitamin D Receptor Genetic Variations May Associate with the Risk of Developing Late Fracture-Related Infection in the Chinese Han Population - Xing-qi Zhao; Kun Chen; Hao-yang Wan; Si-ying He; Han-jun Qin; Bin Yu; Nan Jiang (Journal of Immunology Research)
Variations in the vitamin D receptor (VDR) gene are related to several inflammatory disorders. However, the potential links between such alternations and the risk of developing late fracture-related infection (FRI) remain unclear. This study investigated associations between genetic variations in the VDR and susceptibility to late FRI in the Chinese Han population. Between January 2016 and December 2019, 336 patients with late FRI and 368 healthy controls were genotyped six VDR genetic variations, including ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), TaqI (rs731236), GATA (rs4516035), and Cdx-2 (rs11568820). Significant associations were observed between rs7975232 and FRI susceptibility in the recessive (P=0.019, OR=0.530, 95% CI 0.310–0.906) model. Patients with AA genotype had a relatively higher level of serological vitamin D (20.6 vs. 20.3 vs. 17.9 ng/ml) (P=0.021) than those of AC and CC genotypes. Although no statistical differences were observed, potential correlations may exist between rs1544410 (dominant model: P=0.079, OR=0.634), rs2228570 (dominant model: P=0.055, OR=0.699), and rs4516035 (dominant model: P=0.065, OR=1.768) and the risk of FRI development. In the Chinese cohort, ApaI was associated with a decreased risk of developing FRI, and patients with the AA genotype had a higher vitamin D level. Further studies are required to assess the role of genetic variations in BsmI, FokI, and GATA in the pathogenesis of late FRI.